Witchcraft and Transnational Social Spaces: Witchcraft Violence, Reconciliation and Development in South Africa's Transition Process - Dirk Kohnert (Journal of Modern African Studies, 2003)
The strange collusion between occult belief systems and different trans-national social networks, embedded in specific transformations of local and global modes of production, results in unique but reinforcing modifications of witchcraft belief, its underlying structures and its impact on the process of democratisation. The amazing range of possible results has been indicated by the analysis of two outstanding examples of witchcraft violence in South Africa in times of transition: in the former homelands of Venda and Lebowa, seemingly `traditional' elements of witchcraft accusations, mediated by a misguided struggle for liberation, stimulated the sympathetic attention of stakeholders beyond the local setting. On the other hand, the occult base of violence in the Transkei became so blurred by involvement of `modern' elements of globalised markets of violence that it was hardly visible any more, although under cover its repressive effects were still very much alive. These different roots of witchcraft violence had serious repercussions on conflict resolution and genuine reconciliation, the base for any sustainable democratisation and development. – – La collusion étrange entre les systèmes de croyances occultes et les différents réseaux sociaux transnationaux, intégré dans les transformations spécifiques des modes de production locaux et mondiaux, à contribuer au renforcement de croyance de la croyances occultes, ainsi que à la modifications de ses structures sous-jacentes et de son impact sur le processus de démocratisation. L'incroyable éventail de résultats possibles a été indiqué par l'analyse de deux exemples remarquables de la sorcellerie en Afrique du Sud en période de transition : dans les anciens homelands du Venda et Lebowa, des éléments « traditionnels » de l'accusation de sorcellerie, médiée par une lutte malavisée pour la libération, ont stimulé l'attention sympathique des parties prenantes au-delà du cadre local. D'autre part, la base occulte de la violence dans le Transkei est devenue tellement floue, à cause de la participation des éléments «modernes» de la mondialisation des marchés de violence, qu'ilétait à peine plus visible, bien que ses effets répressifs couvert étaient encore très vivante.Ces différentes racines de violence de la sorcellerie ont eu des répercussions graves sur la résolution des conflits et la réconciliation véritable, qui constituent la base de toute démocratisation et du développement durable.
Keywords: N37; O5; Z1; Z12; 300; witchcraft violence; occult belief systems; social stress; reconciliation; South Africa; Sub-Saharan Africa